2019
DOI: 10.1155/2019/8528719
|View full text |Cite
|
Sign up to set email alerts
|

Positive Correlation between Activated CypA/CD147 Signaling and MMP-9 Expression in Mice Inflammatory Periapical Lesion

Abstract: Aim. Cyclophilin A (CypA)/CD147 signaling plays critical roles in the regulation of inflammation and bone metabolism. This study aimed to investigate the participation of CypA/CD147 in mice periapical lesions progression and its relationship with bone resorption. Methodology. Periapical lesions were induced by pulp exposure in the first lower molars of 40 C57BL/6J mice. The mice were sacrificed on days 0, 7, 14, 21, 28, 35, 42, and 49. Mandibles were harvested for X-ray imaging, microcomputed tomography scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Notably, this study only demonstrated the in vitro production of inflammatory cytokines via the CypA/CD147/ERK/NF-κB pathway by SV-HUC-1 cells stimulated by rMgPa-induced eCypA. Reports have shown that the intervention of CypA/CD147 signaling could probably provide a potential therapeutic and drug target for mice inflammatory periapical lesions progression ( 40 ), Glioblastoma ( 41 ), APE ( 42 ), HCMV ( 43 ), and so on. This study did not investigate the mechanism of interaction between CypA and CD147, the elucidation of which warrants further detailed studies.…”
Section: Discussionmentioning
confidence: 78%
“…Notably, this study only demonstrated the in vitro production of inflammatory cytokines via the CypA/CD147/ERK/NF-κB pathway by SV-HUC-1 cells stimulated by rMgPa-induced eCypA. Reports have shown that the intervention of CypA/CD147 signaling could probably provide a potential therapeutic and drug target for mice inflammatory periapical lesions progression ( 40 ), Glioblastoma ( 41 ), APE ( 42 ), HCMV ( 43 ), and so on. This study did not investigate the mechanism of interaction between CypA and CD147, the elucidation of which warrants further detailed studies.…”
Section: Discussionmentioning
confidence: 78%
“…Recent study has reported the positive relation of CyPA/CD147 signaling and osteoclast-related MMP-9 expression in mice in ammatory periapical lesions progression (18). Additionally, CyPA inhibitor NIM811 signi cantly reduced MMP-9 secretion during the differentiation process of foam cells, which also suggested the potential association of the CyPA/CD147 and MMP-9 expression.…”
Section: Discussionmentioning
confidence: 88%
“…Considering the important role of CD147 in the regulation of renal brosis, the CyPA binding to the CD147 was also noticed to be involved in the stimulation of renal brosis. Moreover, extracellular CyPA has been described to induce the chemotaxis of T cells, monocytes, and macrophages, which leads to the massive recruitment and in ltration of in ammatory cells in the renal allograft tissues (10,18). It is well known that certain pro-brotic cytokines could be produced and secreted during the in ammatory response, triggering the pathogenesis of organ brosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we predicted that Bsg may be an interacting protein of lnc‐CYB561‐5 and further confirmed this prediction by RNA pulldown and RIP assays in vitro. Bsg, also known as CD147, is expressed in a variety of cell types and is involved in the processes of organ development, wound healing, inflammation and tumour progression 37,38 . Recent studies show that Bsg is highly expressed in several cancer cell types and is associated with tumour size, tumour stage, progression and prognosis 39–41 .…”
Section: Discussionmentioning
confidence: 99%